HOSPITAL BRANDING STRATEGY AND ITS IMPACT ON PATIENT TRUST AND SATISFACTION: A QUANTITATIVE ANALYSIS - Bima Subiakto Rahmani; Syifa Ratnaya Safina; Innocentius Bernarto (Universitas Sarjanawiyata Tamansiswa, 2025)
Aims: This study aims to analyze the influence of Hospital Branding Strategy on Patient Trust and Satisfaction in the context of modern healthcare. In the increasingly competitive hospital industry, branding strategy is a strategic instrument for creating a positive image, increasing patient trust, and strengthening the emotional experience during the service process. Method: This research use quantitative method. Result: The analysis shows that Hospital Branding Strategy has a positive and significant effect on Patient Trust and Satisfaction. These findings demonstrate that a strong hospital image and reputation through effective communication, professionalism of medical personnel, and consistent service quality can simultaneously foster patient trust and satisfaction. A well-managed branding strategy also serves as a guarantee of quality and credibility, strengthening long-term relationships between patients and healthcare institutions. Overall, the results of this study confirm that strengthening hospital branding is not merely a marketing effort, but rather a reputation strategy that plays a crucial role in building patient trust and satisfaction. Hospitals that consistently manage their brands and prioritize patient needs will have a competitive advantage and sustained patient loyalty